A Plasma Coagulation Assay for an Activated Protein C-independent Anticoagulant Activity of Protein S - Wijnen, Merel van; van ’t Veer, Cornelis; Meijers, Joost C.M.; Bertina, Rogier M.; Bouma, Bonno N. (Thrombosis and Haemostasis, 1998)
To study the physiological importance of the activated protein C (APC)-independent anticoagulant activity of protein S, we developed an assay specific for this activity. The ability of protein S to prolong the clotting time in an APC-independent way was expressed as the ratio of the clotting time in a plasma sample divided by the clotting time in the presence of a polyclonal antibody against human protein S (both after 1:1 dilution in protein S-C4BP deficient plasma). The mean protein S-dependent anticoagulant ratio (PSdAR) was 1.53 ± 0.18 in 34 healthy controls, and was significantly lower in 16 heterozygous protein S deficient patients (PSdAR = 1.15 ± 0.09). In plasmas from patients under oral anticoagulant therapy the mean PSdAR was within the range of the control population (1.50 ± 0.18). The mean total protein S antigen level in these plasmas was 58%, suggesting a higher specific APC-independent anticoagulant activity of protein S in these patients than in normals.This functional protein S assay can be used for the laboratory diagnosis of protein S deficiency, and to study the mechanism of the APC-independent anticoagulant activity in plasma.